SEMAKIN BERAGAM SEMAKIN BAIK? ISU KEBERAGAMAN GENDER, KEUANGAN, DAN INVESTASI PERUSAHAAN - Zhafarina Isti Ramadhani; Desi Adhariani (Jurnal Keuangan dan Perbankan, 2017)
This research aimed at investigating the impact of gender diversity on financial performance and investment efficiency in public companies listed in Indonesia Stock Exchange. As there was an increase in the number of women on board of directors and commissioners in several countries including Indonesia, it was important to know whether there was an influence to evaluate the role of gender diversity. The sample consisted of 282 and 253 public companies listed in Indonesia Stock Exchange in 2012 (for two different models). Using secondary data and regression tests to analyze the data, this study did not find the significant impact of gender diversity on financial performance and investment efficiency. This could be interpreted as there were still many things to do to improve the role of gender diversity and women capabilities in the board of commissioners and directors.